Pendampingan Pastoral Kepada Lanjut Usia di HKBP Letare Ciledug - Rumantoh Sibarani (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2020)
ABSTRACT Pastoral Care For Elderly at The Church of HKBP Letare Ciledug. This research is intended to give attention to elderly members of the church at the HKBP Letare Ciledug. HKBP Letare Ciledug is only 11 years old, but many of it’s members are elderly. Seen from an increasingly old age, physical and mental conditions that are declining, experiencing many crises and problems. The elderly crave ther ettention of those closest to them, especially from the church. The authors conducted research and want to provide servis through pastoral assistance that is sustaining and nurturing. The function of sustaining is to help elderly people who are sick or injured in order to survive overcoming the conditions experienced. Function of nurturing is to help the elderly develop the potential given by God to overcome the problems. Sampling was carried out for five elderly members of the church at the HKBP Letare Ciledug. The five members of the congregation interviewed represented the elderly congregation, having different struggles and problems, but had the same problem: limited mobility and activity due to illness and an aging body. This struggle has not been touched by Church service. With pastoral care services, through sustaining and nurturing, whic is done in the form of Group Counseling, by : Ministry of Word and Sacrament, Sermons, Prayer and Whorship, able to help elderly to mature and accept their life problems. In the future, church services to the elderly will develop and advance in the church of HKBP Letare Ciledug.